Analisis Efisiensi Dan Nilai Tambah Agroindustri Tahu di Kota Pekanbaru - Arif Budiman; Jum’atri Yusri; Ermi Tety (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The objectives of this study were: 1) to determine the amount of costs, revenues, profits, and profitability value of tofu agroindustry in Pekanbaru. 2) to determine the level of efficiency of tofu agro industry in Pekanbaru. 3) to determine the added value of tofu agro industry in Pekanbaru. This research was conducted from June 2012 until December 2012. The data collection technique was cencus technique. The respondents of this research were all active tofu entrepreneurs in Pekanbaru. This research used qualitative and quantitative methods. The analysis scopes of this research were costs, revenues, profits, profitability, efficiency, and added values analysis. The results of this research showed that the average total cost of tofu agro industry in Pekanbaru was Rp.69,228,509.33 per month. Total revenues of tofu agro industry in Pekanbaru was Rp.96.147.690,00 per month. Total Profit of tofu agro industry in Pekanbaru was Rp.26,919,181.00 per month. The number 38.88 percent of Profitability value meant that tofu agro industry in Pekanbaru was a profitable industry because the value of profitability > 0. 1.39 Ratio of R / C value meant that every Rp.1.00 costs in the production process of tofu will provide 1.39 times profit. The average added value of small size tofu was Rp.7.607,69/kg. The average added vaue of medium size tofu was Rp.5.578,80/kg. Keywords: Tofu, agroindustry, efficiency, added value